Evaluation of hearing status after type I tympanoplasty (Bangladesh Journal of Otorhinolaryngology, 2020)
Objective: To evaluate hearing outcome after type I tympanoplasty in inactive mucous type of chronic otitis media.Methods: It was a cross-sectional study conducted in the department of Otolaryngology & Head Neck Surgery, Sir Salimullah Medical College and Mitford Hospital, Dhaka, from July 2014 to June 2016. 50 cases were selected by matching inclusion and exclusion criteria. Paired t-test and Z test was used to analyze the variables. P values